Graphene loaded into dental polymers as reinforcement of mechanical properties: A systematic review - Beatriz Danieletto Sahm; Ana Beatriz Vilela Teixeira; Andréa Cândido dos Reis (Elsevier, 2023)
Graphene compounds are incorporated into polymers in order to improve their mechanical properties and in dentistry this modification favors the clinical performance of these materials. The aim of this review was to evaluate graphene compounds, their concentrations, and their effect on mechanical properties as flexural, tensile, and compressive strength and hardness of polymethylmethacrylate (PMMA) and polyether-ether-ketone (PEEK) for dental application. The search was carried out in two steps in PubMed/Medline, Embase, Scopus, and Web of Science databases. The eligibility criteria included studies that incorporated pure graphene compounds into dental polymers and evaluated their mechanical properties. Were found 4984 results, of which 11 articles were included in this review. Graphene compounds: graphene oxide (GO), reduced graphene oxide (rGO), and graphene nanoplatelets (GNP) were incorporated into PMMA and PEEK, in concentrations ranging from 0.1 to 10 wt%. Concentrations lower than 0.75 wt% of GO in PMMA and 1 wt% of GNP in PEEK resulted in increased flexural, tensile, compression strength, and hardness of these polymers. It was concluded that the incorporation of graphene compounds in low concentrations increases dental polymers' mechanical properties.